Identifikasi Pengetahuan, Sikap dan Perilaku tentang Imunitas dan Infeksi di Kelurahan Legok - Muhammad Hidayat; Hesty Hesty; Maimaznah Maimaznah; Iin Indrawati; Vevi Suryenti Putri (3031-8572, 2025)
Body immunity is a very important protection mechanism for humans to fight against pathogens such as viruses, bacteria, and other microorganisms. A strong immune system plays a role in reducing the risk of infection and disease, as well as maintaining overall public health. Public knowledge about how to improve and maintain immunity, such as through healthy eating patterns and hygienic behavior, greatly influences population health. This study aims to identify knowledge, attitudes and behaviors about Immunity and Infection in the community in Legok Village, Jambi City. This research method uses quantitative descriptive involving 100 respondents in Legok Village, Jambi City. Data were collected using a questionnaire covering knowledge, attitudes and behaviors about immunity. The results showed that the majority of respondents had good knowledge about immunity (85%), the majority of respondents showed good knowledge about infection (90%), the majority of respondents had good attitudes towards the importance of maintaining immunity (65%), the majority of respondents had good attitudes towards the importance of preventing infection (68%), the majority of respondents' behavior towards immunity (80%), the majority of respondents' behavior towards infection prevention practices (70%) were good. Respondents routinely vaccinated according to the schedule recommended by the government or health institutions. The conclusion is that the majority of the Legok community in Jambi City has good knowledge of immunity and infection, and the majority of the Legok community's attitudes toward immunity and infection are good.